Tanzanian malignant lymphomas: WHO classification, presentation, ploidy, proliferation and HIV/EBV association - Mwakigonja, Amos R (BioMed Central, 2010)
BACKGROUND: In Tanzania, the International Working Formulation [WF] rather than the WHO Classification is still being used in diagnosing malignant lymphomas (ML) and the biological characterization including the HIV/EBV association is sketchy, thus restraining comparison, prognostication and application of established therapeutic protocols. METHODS: Archival, diagnostic ML biopsies (N = 336), available sera (N = 35) screened by ELISA for HIV antibodies and corresponding clinical/histological reports at Muhimbili National Hospital (MNH) in Tanzania between 1996 and 2006 were retrieved and evaluated. A fraction (N = 174) were analyzed by histopathology and immunohistochemistry (IHC). Selected biopsies were characterized by flow-cytometry (FC) for DNA ploidy (N = 60) and some by in-situ hybridization (ISH) for EBV-encoded RNA (EBER, N = 37). RESULTS: A third (38.8%, 109/281) of the ML patients with available clinical information had extranodal disease presentation. A total of 158 out of 174 biopsies selected for immunophenotyping were confirmed to be ML which were mostly (84. 8%, 134/158) non-Hodgkin lymphoma (NHL). Most (83.6%, 112/134) of NHL were B-cell lymphomas (BCL) (CD20+), of which 50.9%, (57/112) were diffuse large B-cell (DLBCL). Out of the 158 confirmed MLs, 22 (13.9%) were T-cell [CD3+] lymphomas (TCL) and 24 (15.2%) were Hodgkin lymphomas (HL) [CD30+]. Furthermore, out of the 60 FC analyzed ML cases, 27 (M:F ratio 2:1) were DLBCL, a slight majority (55.6%, 15/27) with activated B-cell like (ABC) and 45% (12/27) with germinal center B-cell like (GCB) immunophenotype. Overall, 40% (24/60) ML were aneuploid mostly (63.0%, 17/27) the DLBCL and TCL (54.5%, 6/11). DNA index (DI) of FC-analyzed ML ranged from 1.103-2.407 (median = 1.51) and most (75.0%) aneuploid cases showed high (>40%) cell proliferation by Ki-67 reactivity. The majority (51.4%, 19/37) of EBER ISH analyzed lymphoma biopsies were positive. Of the serologically tested MLs, 40.0% (14/35) were HIV positive, mostly with high (≥40.0%) Ki-67 reactivity. CONCLUSIONS: According to the 2001 WHO Classification, most subtypes are represented in Tanzanian ML. Extranodal presentation was common among MNH lymphoma patients who also showed high aneuploidy, tumor proliferation (KI-67) and EBER positivity. DLBCL was frequent and phenotype heterogeneity appeared similar to observations in Western countries suggesting applicability of established intervention approaches. HIV was apparently associated with high ML cell proliferation but extended studies are needed to clarify this.